DEVELOPING PUBLIC PRIVATE PARTERSHIP MANAGEMENT SCHEME FOR ROADSIDE STATION - Herawati Zetha Rahman; Azaria Andreas; Perdana Miraj Sejatiguna (Jurnal Infrastruktur, 2023)
Services by social infrastructure can include health facilities, recreational facilities, security and fire fighting, arts and cultural centers and other public facilities. This research focuses on the study of social infrastructure namely the Roadside Station adopted from Japanese Michinoeki. As for infrastructure financing, this research is aiming to the use of financing scheme involving the private sector, given the limited budget of the central government through the Ministry of Public Works and Housing in providing roadside station services in several locations in Indonesia. On the other hand, the location of the roadside station also sometimes has its own charm for the private sector because it can become a new tourism locus in the area in the future.The types of services provided by Roadside Station are facilities for resting road users, because they are located on national roads. Besides that, Roadside Station are also a place for the surrounding community to sell local products. Currently the Ministry of Public Works and Housing is building Roadside Station in East Java and in Bali. The development of Roadside Station management schemes is intended to ensure continuity in its function as social infrastructure to meet public needs. In addition, with the existence of a management scheme, this further strengthens the position and function of each party in carrying out their rights and obligations in the development of infrastructure using the financing scheme of the Public Private Partnership (PPP). From the institutional scheme produced, it is determined that there are 2 types of Roadside Station management schemes namely, 1) Roadside Station that have been built by the Ministry of Public Works and Housing (PPP – Operation & Maintenance), and 2) Roadside Station to be built by Regional Governments (PPP – Built Operate Transfer).